Analysis of the Ethics of Justice in the Philosophy of Law in the View of Thomas Aquinas - Yosep Copertino Apaut (Jurnal Restorasi : Hukum dan Politik, 2024)
This research aims to determine the ethics of justice in legal philosophy according to the views of Thomas Aquinas.The research method used in this research is a normative legal research method through descriptive literature study utilizing library sources to collect data. How to collect data for this research,researchers collect materials such as books, articles, journals and writings of experts to study and understand the theory after data collection,the researcher will analzqe and add important information that is appropriate to the study. The method of analysis through a historical and philosophical approach to the relationship of natural law in people’s lives, to the basic changes regarding the role of law as ius quia iussum to jus quai iustum and the impact of legal philosophy according to Thomas Aquinas, can build legal methods that are more just and honest, and create a more balanced society, harmony and prosperty.